(untitled) (Journal of Parents and Teachers, 2026)
A child’s environment influences their development, both in terms of their personality and cognitive abilities. To ensure healthy development, more flexible and modular spaces are recommended that can be adapted to the needs of each stage of development. Some of Piaget’s theories are mentioned, in which he emphasizes the importance of space as a safe place for children to experiment.